Sources of cigarettes for youth smokers in Malaysia: Findings from the National Health and Morbidity Survey (NHMS) 2022: Adolescents Health Survey (AHS) - Kuang Hock Lim; Yoon Ling Cheong; Kuang Kuay Lim; Jia Hui Lim; Hamizatul Akmal Abdul Hamid; Mohd Ruhaizie Riyadzi; Sumarni Mohd Ghazali; Chee Cheong Kee; Cheah Yong Kang; Chong Shao Hui; Ali Aman Marine; Mohd Hazilas Mat Hashim; et al. (Tobacco Induced Diseases)
Introduction Developing effective intervention programs to lower adolescent smoking requires a thorough understanding of the sources and methods of youth tobacco product acquisition. This study aimed to identify the sources of cigarettes and related variables among adolescent smokers in Malaysian schools using the latest national data from the National Health and Morbidity Survey: Adolescents Health (NHMS: AHS) 2022.